(untitled) (Cadernos de Sociomuseologia, 2026)
This article critically analyzes the process of constructing the Collection Management Policy of the Coffee Museum, conceived in 2019, from the theoretical-methodological perspective of Sociomuseology and in dialogue with feminist epistemologies. Starting from the understanding that museological guiding documents constitute ethical-political devices and not merely technical instruments, the study examines the listening and conceptualization processes that underpinned the institutional policy, seeking to identify to what extent gender issues—especially the role and representation of women in the coffee industry—were incorporated. It articulates references such as the new definition of museum from the International Council of Museums (ICOM), the UNESCO Recommendation on Museums and Collections, the Sustainable Development Goals, with emphasis on SDG 5, and theoretical contributions from Simone de Beauvoir, Judith Butler, Maria Cristina Oliveira Bruno, Mário Moutinho, and Judite Primo. The analysis highlights relevant conceptual advances, especially in the recognition of historical gaps and silences, but also points to structural limitations in the incorporation of gender as a structuring axis of policy. It concludes that the Collection Policy of the Coffee Museum expresses an institutional process in dispute, situated between synergies and confrontations, revealing potential for future transformations in the field of Sociomuseology and gender studies. Keywords: Sociomuseology; Museums; Gender; Collection policy; Coffee; Cultural heritage.